BatikEvo / Rohayu Daud - Daud, Rohayu (Faculty of Art and Design, 2021)
The batik is one of many popular handicraft products. Batik is always synonymous with a technique or medium using wax and coloured dye. Batik refers to decorative fabrics containing various colours and patterns. The term ‘batik’ is derived from the Javanese word ‘tick’, meaning to drip or write points. While Malaysia is not the only country to produce batik in the region, the style and end product of Malaysian batik differs from other styles in the region. In my artwork, hand drawing techniques are utilised to create paintings on white cloth through the use of chanting. The technique charts patterns with hot wax and then coloured dyes the fabric to suit the pattern. The design, referring to the design concept or inlaid decorative patterns of batik. Two principal motifs are used in this artwork batik design : the organic and the geometric motif. Therefore, painting batik was defined as a painting that applied the visual appearances or images from batik motifs and patterns. Motif and pattern are frequently used to discuss repetition in art. Rhythm is also presented when regulated units are repeated. However this artwork is an evolution medium and technique with the conventional technique batik painting (Image A) that illustrates the aesthetic values of the Malay traditional batik design. Seven (7) motifs are repeatedly utilized in this painting. It consists of a flora mapping with pucuk rebung (bamboo shoots) motif that is known through the triangular shapes.